FILM SEBAGAI DIPLOMASI BUDAYA? - Iva Rachmawati (Jurnal Studi Diplomasi dan Keamanan, 2019)
The power of movies are believed to be able to change the perception of international public  towards particular country.  Movies then became a popular thing as part of a country's cultural diplomacy because of its huge influence nowadays. A number of countries put movies as part of their cultural diplomacy. Likewise with Europe, which began to use Europe on Screen  (EoS) as part of its cultural diplomacy. However, the debate about cultural diplomacy appears to be related to the objectives of cultural diplomacy itself. Some academicians believe that diplomacy is always related to the political goals of the state, while others believe that cultural diplomacy must be distinguished from other diplomatic activities because the aim is merely to foster mutual understanding and harmony through the introduction of culture. This article was written to understand the concept of cultural diplomacy and to know whether a movie can be part of cultural diplomacy, especially activities organized by Europe on Screen. This article will be presented by tracing back what is meant by cultural diplomacy and how the practice of cultural diplomacy through movies by a number of countries. By referring to the conception of cultural diplomacy and the practice of using movies by a number of countries, this article puts Europe on Screen as part of cultural diplomacy not because of the movies itself but from the overall project activities of the EoS.